2017
DOI: 10.1007/s00421-017-3643-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence in the human of a hypotensive and a bradycardic effect after mouth opening maintained for 10 min

Abstract: This study shows that, in normotensives, a single fixed submaximal mouth opening for 10 min is followed by prolonged albeit small reductions of blood pressure and heart rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
4
7
1
Order By: Relevance
“…Another possibility is that the effect is mediated by nitric oxide (NO). Previous studies have demonstrated that a mandibular extension very similar to that applied in our subjects, was able to substantially lower the systemic blood pressure in humans, and lead to an increase in the NO plasma levels in the rat ( Brunelli et al, 2012 ; Lapi et al, 2013 , 2014 , 2016 , 2017 ; Del Seppia et al, 2016 , 2017 ). Notably, NO has been implicated in pain transmission ( Rosenthal et al, 2015 ), and in some cases NO donors have been shown to produce antinociceptive effects, while NO synthase inhibitors lead to pain ( Yeo, 2002 ; da Silva et al, 2008 ; Fan et al, 2009 ).…”
Section: Discussionmentioning
confidence: 55%
“…Another possibility is that the effect is mediated by nitric oxide (NO). Previous studies have demonstrated that a mandibular extension very similar to that applied in our subjects, was able to substantially lower the systemic blood pressure in humans, and lead to an increase in the NO plasma levels in the rat ( Brunelli et al, 2012 ; Lapi et al, 2013 , 2014 , 2016 , 2017 ; Del Seppia et al, 2016 , 2017 ). Notably, NO has been implicated in pain transmission ( Rosenthal et al, 2015 ), and in some cases NO donors have been shown to produce antinociceptive effects, while NO synthase inhibitors lead to pain ( Yeo, 2002 ; da Silva et al, 2008 ; Fan et al, 2009 ).…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies in normotensive rats, investigating arteriolar tone modifications, have shown that the stimulation of trigeminal nerve by ME procedure determines a prolonged hypotensive effect accompanied by initial rapid vasoconstriction, followed by a prolonged vasodilation y in the pial microcirculation ( Lapi et al, 2017 ). Furthermore, our studies on humans demonstrated that the submaximal mouth opening for a relatively brief time (10 min) was followed by a prolonged hypotensive and bradycardic effect on normotensive volunteers ( Del Seppia et al, 2016 , 2017 ). Due to the important role of RAS in the pathophysiology of hypertension, we focused on the gene expression and protein levels of RAS components during ME protocol at cortex level in SHRs and in NT rats.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, stimulation of specific facial regions may induce reflex with certain important implications ( Brunelli et al, 2012 ). Recently, we showed that, in normotensive anesthetized rats and in normotensive humans, a mandibular extension (ME) induced a reduction in blood pressure (BP) ( Lapi et al, 2013 , 2014 ; Del Seppia et al, 2016 , 2017 ). Moreover, in normotensive rats, this effect was abolished by bilateral peripheral trigeminal section, thus indicating a fundamental role of trigeminal nerve in the hypotensive ME-induced response ( Lapi et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…), and another with a fixed mouth opener, defined static extension (Del Seppia et al. ), however, a similar study by other authors using dynamic extension failed to confirm these results (De Innocentiis et al. ).…”
Section: Introductionmentioning
confidence: 91%